2015
DOI: 10.1186/s12985-014-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disinfectants to prevent mechanical transmission of viruses and a viroid in greenhouse tomato production

Abstract: BackgroundIn recent years, a number of serious disease outbreaks caused by viruses and viroids on greenhouse tomatoes in North America have resulted in significant economic losses to growers. The objectives of this study were to evaluate the effectiveness of commercial disinfectants against mechanical transmission of these pathogens, and to select disinfectants with broad spectrum reactivity to control general virus and viroid diseases in greenhouse tomato production.MethodsA total of 16 disinfectants were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 40 publications
5
29
2
2
Order By: Relevance
“…A lower efficiency in inactivating CGMMV, shown in seedling inoculation studies, was obtained with Virkon S and the efficiency in disinfecting grafting knives was not high as well (Table 1; Figure 2). Unlike our results, Virkon S was reported as an efficient disinfectant for disease spread by the tobamoviruses tobacco mosaic virus (TMV) and tomato mosaic virus (ToMV) (Li et al, 2015). Interestingly, active oxygen (Huwa‐San) 1% solution was highly efficient in disinfecting sowing trays (Table 3) but was insufficient as a disinfectant of grafting knives and in CGMMV inactivation assays (Figure 2; Table 1).…”
Section: Discussioncontrasting
confidence: 96%
“…A lower efficiency in inactivating CGMMV, shown in seedling inoculation studies, was obtained with Virkon S and the efficiency in disinfecting grafting knives was not high as well (Table 1; Figure 2). Unlike our results, Virkon S was reported as an efficient disinfectant for disease spread by the tobamoviruses tobacco mosaic virus (TMV) and tomato mosaic virus (ToMV) (Li et al, 2015). Interestingly, active oxygen (Huwa‐San) 1% solution was highly efficient in disinfecting sowing trays (Table 3) but was insufficient as a disinfectant of grafting knives and in CGMMV inactivation assays (Figure 2; Table 1).…”
Section: Discussioncontrasting
confidence: 96%
“…It has been shown that CaMV can stay for hours on surfaces such as doors, phones, and gloves, and can be exchanged by hand-shaking (Jiang et al, 1998;Dancer, 2014), so disinfecting tools, equipment, and anything that contacts plants will reduce infection. Though it did not include CaMV, a study that tested how to prevent propagation of plant viruses, such as Pepino mosaic virus (PepMV), Potato spindle tuber viroid (PSTVd), Tomato mosaic virus (ToMV), and Tobacco mosaic virus (TMV), examined sixteen commercially available disinfectants and found that 10% bleach is the most effective solution for preventing viral infection of plants in greenhouse facilities (Li et al, 2015).…”
Section: Camv In Agriculture and Management Practices To Reduce Camv mentioning
confidence: 99%
“…Virion viability experiments revealed that like other tobamoviruses, YTMMV virions are highly resilient. Dried leaf tissue harboured infectious virions for at least 1 year at ambient temperatures, −80 and 22 ° C. Treatment with milk solution and NaOH solution, both compounds previously described as being effective for decontaminating tools of tobamoviruses (Nitzany, ; Hu et al ., ; Kamenova & Adkins, ; Lewandowski et al ., ; Li et al ., ), were largely ineffective for YTMMV. Dry heating of infected leaf materials was an effective phytosanitary measure, but only after exposure to 160 ° C for 5 days.…”
Section: Discussionmentioning
confidence: 98%
“…Both 0.1 m NaOH and 20% w/v skimmed milk were ineffective at decontaminating YTMMV‐infected tools when incubated for 30 min. Milk treatment was reported to completely inactivate hibiscus latent Fort Pierce virus (HLFPV) (Kamenova & Adkins, ), TMV (Lewandowski et al ., ; Li et al ., ) and ToMV (Li et al ., ), but was ineffective in some cases with TMV (Crowley, ; Denby & Wilks, ). Milk contains casein and whey, proteins that inactivate virions (Hagborg & Chelack, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation